Roll-to-roll printing trench-like metasurface film for radiative cooling - Yaoguang Ma (Light: Science & Applications, 2023)
Abstract A Roll-to-roll technology can enable the fabrication of trench-like photonic meta-structures that are strongly absorptive in the MIR region, providing a controllable optical response for diurnal radiative cooling.